INTERMEDIAL INDIAN OCEAN - In Conversation with Nalini de Sousa & Pedro Pombo (Workshop Intermedial Indian Ocean - 2021, 2023)
As part of the Indian Ocean events in November 2021, filmmaker Nalini Elvino De Sousa and anthropologist Pedro Pombo were guests of the Africa Multiple Cluster of Excellence in Bayreuth. In this interview, they talk with Prof. Dr. Ute Fendler, Deputy Spokesperson of the Cluster, and Clarissa Vierke, Professor of Literatures in African Languages at the University of Bayreuth, about their documentary film “The Club”. "The Club" portrays the life of Goans in Tanzania and the cultural club that united them. The film team followed families recounting their memories of the club in Dar es Salaam, from the traditions that were maintained there to the music they listened to together.